Obesity and strength exercises in children: body composition influence - Fernández-García, José Carlos; Álvarez-Carnero, Elvis; Warnberg, Julia; Alvero-Cruz, José Ramón (Karger, 2013)
Great levels of explosive dynamic strength (EDS) are needed to improve intermittent physical activity (PA) performance. Isometric strength (IS) has been associated with healthier metabolic and body composition profiles. Hence, interactions between strength performances and body composition would be explaining differences normal and overweight-obese boys (OB). The aim of this study was to compare EDS and IS between NB and OB.
Keywords: Obesidad en niños; Children; Obesity; Strength; Body composition